2016
DOI: 10.3389/fpls.2016.00101
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric Bacterial Strain Brevibacterium casei MH8a Colonizes Plant Tissues and Enhances Cd, Zn, Cu Phytoextraction by White Mustard

Abstract: Environmental pollution by heavy metals has become a serious problem in the world. Phytoextraction, which is one of the plant-based technologies, has attracted the most attention for the bioremediation of soils polluted with these contaminants. The aim of this study was to determine whether the multiple-tolerant bacterium, Brevibacterium casei MH8a isolated from the heavy metal-contaminated rhizosphere soil of Sinapis alba L., is able to promote plant growth and enhance Cd, Zn, and Cu uptake by white mustard u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The most common method to compare soil remediation in different treatments is to take samples at selected time intervals and compare the measured variables, such as microbial communities, between sampling dates [ 38 , 59 61 ]. As the rate of soil remediation is dependent on soil type, it is conceivable that only the time-dependent changes are reported or noticed, and the microbial community changes connected to actual degradation are ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The most common method to compare soil remediation in different treatments is to take samples at selected time intervals and compare the measured variables, such as microbial communities, between sampling dates [ 38 , 59 61 ]. As the rate of soil remediation is dependent on soil type, it is conceivable that only the time-dependent changes are reported or noticed, and the microbial community changes connected to actual degradation are ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these interactions are mutualistic. For example, plants benefit from mobilization of minerals ( Vangronsveld et al, 2009 ; Sessitsch et al, 2013 ; Plociniczak et al, 2016 ) and other inorganic molecules, while the microbes benefit from root exudates which provide an energy source in the form of sugars and organic acids ( Bais et al, 2006 ; van Dam and Bouwmeester, 2016 ). Plant hosts further benefit from microbes with improved growth ( Bashan et al, 2014 ; Glick, 2014 ), drought and salt tolerance ( Castiglioni et al, 2008 ; Kasim et al, 2013 ; Han et al, 2014 ; Naveed et al, 2014 ; Sarma and Saikia, 2014 ; Pinedo et al, 2015 ), and protection against soilborne pathogens ( Weller et al, 2002 ; Cha et al, 2015 ; De Boer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…JYX10 significantly improved Zn uptake by B. napus . Recently, Płociniczak et al (2016) also reported that Brevibacterium casei MH8a colonized white mustard plant tissues and enhanced Cu and Zn phytoextraction.…”
Section: Resultsmentioning
confidence: 95%
“…Despite numerous reports about rhizobacteria-enhanced phytoremediation of heavy metals ( Sheng and Xia, 2006 ; Dell’Amico et al, 2008 ; Płociniczak et al, 2016 ), little information is available about effects Cu/Zn-resistant bacteria from the rhizosphere of S. oleraceus on plant growth and heavy metal bioavailability/biosorption in multi-metal-polluted soils. Thus, the quest for novel, beneficial and indigenous rhizobacteria among different plant species grown in multi-metal-polluted environments is very meaningful.…”
Section: Introductionmentioning
confidence: 99%